Seasonal variation of ewe body condition in extensive production systems of Northeastern Portugal - Azevedo J.M.T.; Silva S.R. (Changes in sheep and goat farming systems at the beginning of the 21st century : research, tools, methods and initiatives in favour of a sustainable development, 2009)
During four years, 2 flocks of autochthonous Churra Galega Bragançana (CB) and Churra da Terra Quente (CTQ) breeds with 87 ± 29 and 93 ± 13 ewes were studied. These flocks are managed in the traditional extensive systems followed in the Northeast of Portugal. The body condition score (BCS) was recorded monthly using the method proposed by Russel et al. (1969). The results for both flocks show that BCS in 9 to 12 months are below note 3 in more than 73 percent of the ewes. The better BCS was observed at the spring (55 and 43 percent of ewes with BCS of 3 or 4 for CB and CTQ, respectively). The results show that the traditional production system allows significant seasonal body condition variation and low body condition of ewes during a great part of the year.
Proceedings of the Seminar of the Subnetwork on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2007/11/15-17, Ponte de Lima (Portugal)